Concentrations of rare earth elements in maternal serum during pregnancy and risk for fetal neural tube defects. (April 2020) - Wei, Jing; Wang, Chengrong; Yin, Shengju; Pi, Xin; Jin, Lei; Li, Zhiwen; Liu, Jufen; Wang, Linlin; Yin, Chenghong; Ren, Aiguo
Highlights: This study explored the associations between 10 REEs and risk for fetal NTDs. Higher concentrations of La were associated with an increased risk for NTDs. The risk for NTDs increased with overall levels of the 10 elements as a mixture. Abstract: Rare earth elements (REEs) are ubiquitous in the environment. Animal experiments have shown that many REEs have adverse impacts on the health of fetuses. However, data from humans are scarce. In this study, we examined the associations between concentrations of 10 REEs in maternal serum and the risk for fetal neural tube defects (NTDs). The study included 200 pregnant women with pregnancies affected by NTDs and 400 pregnant women with healthy fetuses/infants. Fifteen REEs in maternal serum were assessed; 10 of them were detectable in over 60% of samples and were included in statistical analyses, including lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), lutetium (Lu), and yttrium (Y). When the elements were considered individually with the use of Logistic regression model, the risk for NTDs increased by 2.78-fold (1.25–6.17) and 4.31-fold (1.93–9.62) for La, and 1.52-fold (0.70–3.31) and 4.73-fold (2.08–10.76) for Ce, in the second and third tertiles, respectively, compared to the lowest concentration tertile. When Bayesian kernel machine regression was used to examine the joint effect of exposure to all 10 REEs, the risk for NTDs increased with overall levels of these REEs and the association between La and NTD risk remained when other nine elements were taken into consideration simultaneously. Taken together, this study shows that the risk for NTDs increases with La concentrations when single REEs are considered and with concentrations of all 10 REEs when these REEs are considered as a co-exposure mixture.